Ligand partitioning into lipid bilayer membranes under high pressure: Implication of variation in phase-transition temperatures. (December 2017) - Matsuki, Hitoshi; Kato, Kentaro; Okamoto, Hirotsugu; Yoshida, Shuntaro; Goto, Masaki; Tamai, Nobutake; Kaneshina, Shoji
Graphical abstract: Highlights: The variation in phase-transition temperatures of DPPC bilayer membrane by adding two membrane-active ligands was studied. PA has strong affinity with the lamellar gel phase while HAL has strong affinity with the liquid crystalline phase. The transfer volumes of PA into the gel and liquid crystalline phases form a striking contrast to those of HAL. PA suppresses while HAL promotes the formation of the interdigitated gel phase under high pressure. The DPPC bilayer membrane has a potential to recognize kinds of ligand molecules. Abstract: The variation in phase-transition temperatures of dipalmitoylphosphatidylcholine (DPPC) bilayer membrane by adding two membrane-active ligands, a long-chain fatty acid (palmitic acid (PA)) and an inhalation anesthetic (halothane (HAL)), was investigated by light-transmittance measurements and fluorometry. By assuming the thermodynamic colligative property for the bilayer membrane at low ligand concentrations, the partitioning behavior of these ligands into the DPPC bilayer membrane was considered. It was proved from the differential partition coefficients between two phases that PA has strong affinity with the gel (lamellar gel) phase in a micro-molal concentration range and makes the bilayer membrane more ordered, while HAL has strong affinity with the liquid crystalline phase in a milli-molal concentration range and does the bilayer membrane more disordered. The transfer volumes of both ligands from the aqueous solution to each phase of the DPPC bilayer membrane showed that the preferential partitioning of the PA molecule into the gel (lamellar gel) produces about 20% decrease in transfer volume as compared with the liquid crystalline phase, whereas that of the HAL molecule into the liquid crystalline phase does about twice increase in transfer volume as compared with the gel (ripple gel) phase. Furthermore, changes in thermotropic and barotropic phase behavior of the DPPC bilayer membrane by adding the ligand was discussed from the viewpoint of the ligand partitioning. Reflecting the contrastive partitioning of PA and HAL into the pressure-induced interdigitated gel phase among the gel phases, it was revealed that PA suppresses the formation of the interdigitated gel phase under high pressure while HAL promotes it. These results clearly indicate that each phase of the DPPC bilayer membrane has a potential to recognize various ligand molecules.